Monoclonal antibodies neutralizing alpha-hemolysin, bicomponent leukocidins, and clumping factor A protected against Staphylococcus aureus-induced acute circulatory failure in a mechanically ventilated rabbit model of hyperdynamic septic shock - Nguyen, Nhu T. Q.; Doan, Thien N. M.; Sato, Kei; Tkaczyk, Christine; Sellman, Bret R.; Diep, Binh An (Frontiers in Immunology, 2023)
Background: Patients with septic shock caused by Staphylococcus aureus have mortality rates exceeding 50%, despite appropriate antibiotic therapy. Our objectives were to establish a mechanically ventilated rabbit model of S. aureus septic shock and to determine whether a novel immunotherapy can prevent or halt its natural disease progression. Methods: Rabbits were ventilated with lung-protective low-tidal volume, instrumented for advanced hemodynamic monitoring, and characterized for longitudinal changes in acute myocardial dysfunction by echocardiography and sepsis-associated biomarkers after S. aureus intravenous challenge. To demonstrate the potential utility of this hyperdynamic septic shock model for preclinical drug development, rabbits were randomized for prophylaxis with anti-Hla/Luk/ClfA monoclonal antibody combination that neutralizes alpha-hemolysin (Hla), the bicomponent pore-forming leukocidins (Luk) including Panton-Valentine leukocidin, leukocidin ED, and gamma-hemolysin, and clumping factor A (ClfA), or an irrelevant isotype-matched control IgG (c-IgG), and then challenged with S. aureus. Results: Rabbits challenged with S. aureus, but not those with saline, developed a hyperdynamic state of septic shock characterized by elevated cardiac output (CO), increased stroke volume (SV) and reduced systemic vascular resistance (SVR), which was followed by a lethal hypodynamic state characterized by rapid decline in mean arterial pressure (MAP), increased central venous pressure, reduced CO, reduced SV, elevated SVR, and reduced left-ventricular ejection fraction, thereby reproducing the hallmark clinical features of human staphylococcal septic shock. In this model, rabbits pretreated with anti-Hla/Luk/ClfA mAb combination had 69% reduction in mortality when compared to those pretreated with c-IgG (P<0.001). USA300-induced acute circulatory failure—defined as >70% decreased in MAP from pre-infection baseline—occurred in only 20% (2/10) of rabbits pretreated with anti-Hla/Luk/ClfA mAb combination compared to 100% (9/9) of those pretreated with c-IgG. Prophylaxis with anti-Hla/Luk/ClfA mAb combination halted progression to lethal hypodynamic shock, as evidenced by significant protection against the development of hyperlactatemia, hypocapnia, hyperkalemia, leukopenia, neutropenia, monocytopenia, lymphopenia, as well as biomarkers associated with acute myocardial injury. Conclusion: These results demonstrate the potential utility of a mechanically ventilated rabbit model that reproduces hallmark clinical features of hyperdynamic septic shock and the translational potential of immunotherapy targeting S. aureus virulence factors for the prevention of staphylococcal septic shock.